Otosclerosis - Clinic and imagiologic correlation - Amaro, Carla D'Espiney (2010)
Objectives: Identify factors that might influence post-operative results in stapes surgery, as the computed tomography (CT) images.Patients and Methods: Retrospective study of 42 patients. Statistical analysis with the T Student and the Pearson Correlation studies.Results: The medium air-bone gap (GAO) pre and post-operative was 42 dB and 13 dB respectively. From the 11 CT evaluated, 4 had active focus and 5 had inactive focus. In 1 CT, the image was considered normal. In 7 ears, the focus was type 1. There was no statistical significance between hearing results and the presence of Carhart notch and the pre-operative GAO (p>O.O5). Although there was some positive correlation between the focus activity showed by CT and the hearing results, this was not statistically significant.Conclusion: CT scan can be helpful in treatment decisions in otosclerosis.